The Relationship Of Knowledge Of Women Who Have Toddlers About Fulfillment Of Balanced Nutrition To Prevention Of Stunting In Bonan Village Dolok I Sijamapolang District Humbang Hasundutan District Year 2023 - Mayes Felda Simamora; Nova Sontry Node Siregar; Helprida Sihite (International Journal of Health Engineering and Technology, 2023)
One of the health problems being addressed in Indonesia is stunting. In 2019 the prevalence of stunting in Indonesia was 27.7% and in 2021 it has decreased to 24.4%. In Humbang Hasundutan Regency, the prevalence of stunting is (14.38%). When the initial survey was conducted, the number of stunted toddlers in Bonandolok I Village was 11 toddlers. There are 4 things that cause stunting, namely: knowledge, parenting, basic sanitation, and administration of deworming drugs. The purpose of this study was to determine the relationship between the knowledge of mothers who have toddlers about fulfilling balanced nutrition and the prevention of stunting in Bonandolok I Village, Sijamapolang District, Humbang Hasundutan Regency in 2023. This type of research is a descriptive analytic cross-sectional design. Held in March-May 2023 in Bonandolok I Village, Sijamapolang District. The population is a group of mothers who have babies and toddlers in Bonandolok I Village in 2023 with a total of 49 respondents. The sampling technique is total sampling and chi-square test. The results showed that there was a relationship between knowledge and stunting prevention. The results of the chi-square test x^2 count (17,845) <x^2 table (4,605) were obtained. There is a relationship between parenting style and stunting prevention, the results of the chi-square test x^2 count (21,248) <x^2 table (4,605). There is a relationship between basic sanitation and the prevention of stunting, the results of the chi-square test x^2 count (16,079) <x^2 tables (2,705), and there is a relationship between the administration of deworming medication and the prevention of stunting, the results of the chi-square test x^2 count (14,968) <x^2 table (2,705). It is hoped that respondents will learn more about how to prevent stunting